Economic growth and the balance-of-payments constraint: The case of the Spanish regions, 1988-2008 - Oscar Bajo-Rubio; Carmen Diaz-Roldan (European Regional Science Association (ERSA), 2010)
The balance of payments can act as a constraint to the rate of growth of output, on putting a limit to the growth in the level of demand to which supply can adapt. This effect might be even stronger for regional economies, presumably more integrated among them. In this paper, we examine this issue for the case of the Spanish regions over the period 1988-2008, and calculate their balance of payments-constrained growth rates. By comparing these balance of payments-constrained growth rates with the actual growth rates, we would be able to assess whether the balance of payments has acted as a constraint to economic growth for the Spanish regional economies in the period analyzed.
Keywords: F41; F43; O40; 330; Economic growth; External deficit; Spanish regions